(untitled) - Blauert, Jens (Heidelberg, 2009)
"Acoustics for Engineers" is designed for extensive teaching at the university level. Under the guidance of an academic teacher it is sufficient as the sole textbook for the subject. Each chapter deals with a well defined topic and represents the material for a two-hour lecture. The 15 chapters alternate between more theoretical and more application-oriented concept
Keywords: Acoustical engineering,Kỹ thuật âm thanh